Internalization of Pancasila Student Profile Values based on Digital Citizenship as Preparation for Industry 4.0 and Implementation of Independent Learning Policy - Ardhana Januar Mahardhani; Muhamad Abdul Roziq Asrori (STAI Hubbulwathan Duri, 2023)
Character education is an interesting issue in preparing children at the elementary school level to become a digital-based global society. This study aims to describe the process of Internalization of Pancasila student profile values based on digital citizenship preparation for the industrial era 4.0 and Merdeka Belajar case study at a state elementary school in Kepuhrejo. This is a case study with data from observations, interviews, and documentation involving 13 key informants, namely the principal, 6 classroom teachers, and 6 students who were previously determined based on the required criteria. Data analysis is carried out by interacting with existing data: reduce, present, and conclude. For the validity of the data, triangulation was carried out. The results of the study show that the planning process utilizes the results of the discussion from the teacher working group combined with literacy needs in the 4.0 era. The implementation uses an internalization approach that emphasizes habituation, direct experience, and exemplary both in the classroom and outside the classroom to strengthen data, technology and human literacy as a form of digital citizenship approach preparation for the industrial era 4.0